2020
DOI: 10.3390/ijerph17051633
|View full text |Cite
|
Sign up to set email alerts
|

Potential Factors Influencing Repeated SARS Outbreaks in China

Abstract: Within last 17 years two widespread epidemics of severe acute respiratory syndrome (SARS) occurred in China, which were caused by related coronaviruses (CoVs): SARS-CoV and SARS-CoV-2. Although the origin(s) of these viruses are still unknown and their occurrences in nature are mysterious, some general patterns of their pathogenesis and epidemics are noticeable. Both viruses utilize the same receptor-angiotensin-converting enzyme 2 (ACE2)-for invading human bodies. Both epidemics occurred in cold dry winter se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
162
2
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(184 citation statements)
references
References 39 publications
7
162
2
13
Order By: Relevance
“…Climate and local environmental conditions may also affect the speed of local transmission and can lead to deviations from the expected number of infections. Such an association has been suggested for SARS and MERS [34], but has not yet been demonstrated in the case of COVID-19. It is still not clear how the virus reacts to temperature or air pollution, especially particulates.…”
Section: Limitations To Predictive Capacitymentioning
confidence: 92%
“…Climate and local environmental conditions may also affect the speed of local transmission and can lead to deviations from the expected number of infections. Such an association has been suggested for SARS and MERS [34], but has not yet been demonstrated in the case of COVID-19. It is still not clear how the virus reacts to temperature or air pollution, especially particulates.…”
Section: Limitations To Predictive Capacitymentioning
confidence: 92%
“…Pathogens of the above diseases are species in the genus of Betacoronavirus belonging to the family Coronaviridae in the order Nidovirales [8]. Collaborative research from epidemiology and etiology, including identifying pathogens, tracking sources, and clinical prevention and treatment including vaccines and antivirus medicine discovery, are urgent [9,10]. Bibliometrics based on the mapping knowledge domain as a tool to evaluate the research outputs' characteristics has been widely adopted, and analysis results are capable of providing a comprehensive assessment of the quality and quantity of scientific yields [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic studies and sequence analyses of SARS-CoV-2 and some SARS-related CoVs revealed that all use ACE2 as the host cell receptor [63]. Evolutionary, human SARS-CoVs and bat SARS-CoVs such as LYRa11, Rs3367, Rf1, Cp and Rp3 share a common ancestor, while SARS-CoV and MERS-CoV are distantly related to each other [64,65]. Receptor-binding domain (RBD) of S protein, which is responsible for binding to ACE2 of cell host receptor, is considered as the major part evolving in the beta CoVs so 29 unique RBDs were phylogenetically identified in three distinct clades [66].…”
Section: Introductionmentioning
confidence: 99%